Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. Administrative empowerment and its relationship to organizational commitment among female leaders in the Ministry of EducationNourah Khaled Muhammad Anzan 2. The Role of the primary school in the Qassim educational region in activating the practices of the green school from the point of view of the teachersMaha Dahlos Alharbi, Najla Mohammed Alhodaif 3. The Organizational Effectiveness in Community Colleges in Light of The Pounder Model: A Field Study in The Kingdom of Saudi Arabia in 1443 AHAmal Hoshan Al-Hoshan 4. The Impact of the Attractive Authority of High School Teachers in Developing the Leadership Skills of Students in JordanNabeela Abdallah Ghaithian Alshawabkeh 5. Teachers' attitudes towards the use of educational games in developing creative thinking among children in Hafr Al-BatinNouf Nahar Al-Mutairi 6. The effect of hypothetical case law in the development of the situational approachOmar Bychou 7. E-Learning Pattern Between Effectiveness and Obstacles as Viewed by Secondary School Students During the COVID-19 Pandemic in JordanNofah Sameh Al-Mawadeh, Mutaz Nayef Alsnayan, Majid Mohammad ALkhtaybeh
Keywords: Journal of Educational and Psychological Sciences